2017
DOI: 10.1080/07359683.2017.1309212
|View full text |Cite
|
Sign up to set email alerts
|

What’s in a name? Group fitness class names and women’s reasons for exercising

Abstract: The benefits of intrinsic exercise motivation are well recognized, yet extrinsically focused group-fitness class names/descriptions dominate the fitness industry. To explore the impact of how fitness classes are marketed, women (N = 389) were asked to indicate their preference for either intrinsically or extrinsically focused fitness classes based on title/description. Participants who favored intrinsic class names/descriptions were more likely to report greater interest/enjoyment, perceived competence, and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…A challenge with such recruitment is that non-members perceive that there is a high focus on body appearance among members of fitness centers, and as such, this prevents them from involving with this industry (Credicare, 2016). Such perceptions may be derived from the appearancefocused communication operated by the fitness industry in their marketing strategies, and by the exercise concepts consecutively introduced in the last decade (e.g., bootylicious, body pump, booty builder, 500 kcal) (Brown et al, 2017). Other than the limitation such reputation may bring for the fitness industry upon the potential to recruit new members, this also brings concern to the health of fitness instructors [i.e., group instructors (GIs) and personal trainers (PTs)] working in such environment on a daily basis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A challenge with such recruitment is that non-members perceive that there is a high focus on body appearance among members of fitness centers, and as such, this prevents them from involving with this industry (Credicare, 2016). Such perceptions may be derived from the appearancefocused communication operated by the fitness industry in their marketing strategies, and by the exercise concepts consecutively introduced in the last decade (e.g., bootylicious, body pump, booty builder, 500 kcal) (Brown et al, 2017). Other than the limitation such reputation may bring for the fitness industry upon the potential to recruit new members, this also brings concern to the health of fitness instructors [i.e., group instructors (GIs) and personal trainers (PTs)] working in such environment on a daily basis.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, when physical activity is driven by external motivation (i.e., motivation comes from outside the individual and is performed to gain a reward, e.g., admiration and popularity), and specifically when motivated by a drive for extreme body figures, it associates to less healthy, and potentially harmful, effects (Thogersen-Ntoumani and Ntoumanis, 2007;Brown et al, 2017). Within the fitness industry, idealization of extreme body figures may typically turn into a desire to attain a thin body figure (Olson et al, 1996), a muscular body figure (i.e., a desire to attain an athletic body figure characterized by large muscle mass) (McCreary and Sasse, 2000), or a lean body ideal (i.e., desire to achieve a toned, athletic body with a low level of body fat) (Smolak and Murnen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In India, the utilisation of such an approach can be easily observed. Its popularisation has resulted from the so-called ‘modernisation’ of yoga, reflected by disregarding the fact that the activity is a derivative of the Buddhist religion, where health and fitness, although valued, are not the main focus of the practice (Larson, 2008; Worthington, 1982) and interpreting it as a purely physical exercise (Brown et al , 2017). Arguably, this strategy is designed to respond to a Western market consisting of people who are conscious about their physical health and attractiveness of their body, but not necessarily interested in any mental or spiritual self-development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For decades, the marketing and promotion of fitness centers, and the services within the centers in particular, has been centered on objectivization of the body (13,14). Specifically, for women this may have contributed to underline the sex role that society traditionally has prescribed for women (i.e., as a sexual object), which may facilitate lower threshold toward sexually related verbal, behavioral, or physical acts (12).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is scarce knowledge on the extent of SH in the fitness industry. We recently reported that a high frequency of fitness instructors experienced body appearance pressure (15), which points to a serious consequence of working within an industry where body appearance has been idealized for decades (13,16). Working on profit-based contracts, relying on a "bodily capital" (i.e., relying on body appearance to win customers, as this may promote credibility on health and exercise knowledge) (14), may increase the risk for experiences of SH.…”
Section: Introductionmentioning
confidence: 99%